Nanohydroxyapatite Exerts Cytotoxic Effects and Prevents Cellular Proliferation and Migration in Glioma Cells. (15th January 2019) - Gorojod, Roxana Mayra; Porte Alcon, Soledad; Dittler, María Laura; Gonzalez, Mónica Cristina; Kotler, Mónica Lidia
Abstract: Hydroxyapatite (Ca10 (PO4 )6 (OH)2 ; HAP) is an essential component of the human bone inorganic phase. At the nanoscale level, nano-HAP (nHAP) presents marked emergent properties differing substantially from those of the bulk counterpart. Interestingly, these properties depend on nanoparticle characteristics. In this study, we investigated the cytotoxicity of rod-shaped crystalline nHAP (10–20 nm × 50–100 nm) in both normal (ARPE-19, BV-2) and tumoral (HepG2, HEp-2, A549 and C6) cells. We found that nHAP was cytotoxic in tumor HEp-2, A549, and C6 cells. Moreover, it induced an expansion of the lysosomal compartment at sublethal concentrations in different cell lines, while lysosomal membrane damage was not detected. In C6 glioma cells, the most sensitive cell line to nHAP, these nanoparticles increased reactive oxygen species (ROS) production and induced DNA damage measured by γ-H2AX phosphorylation. Interestingly, our data also show for the first time that nHAP affects both cell unlimited proliferative capacity and cell migration, two of the major pathways involved in cancer progression. The present results showed the cytotoxic and antiproliferative effects of nHAP and suggest its potential as an alternative agent for glioma therapy.